Genome-Wide Identification and Expression Analysis of Homeodomain Leucine Zipper Subfamily IV (HDZ IV) Gene Family from Musa accuminata - Pandey, Ashutosh; Misra, Prashant; Alok, Anshu; Kaur, Navneet; Sharma, Shivani; Lakhwani, Deepika; Asif, Mehar H.; Tiwari, Siddharth; Trivedi, Prabodh K. (Frontiers in Plant Science, 2016)
The homedodomain zipper family (HD-ZIP) of transcription factors is present only in plants and plays important role in the regulation of plant-specific processes. The subfamily IV of HDZ transcription factors (HD-ZIP IV) has primarily been implicated in the regulation of epidermal structure development. Though this gene family is present in all lineages of land plants, members of this gene family have not been identified in banana, which is one of the major staple fruit crops. In the present work, we identified 21 HDZIV genes in banana by the computational analysis of banana genome resource. Our analysis suggested that these genes putatively encode proteins having all the characteristic domains of HDZIV transcription factors. The phylogenetic analysis of the banana HDZIV family genes further confirmed that after separation from a common ancestor, the banana and poales lineages might have followed distinct evolutionary paths. Further, we conclude that segmental duplication played a major role in the evolution of banana HDZIV genes. All the identified banana HDZIV genes expresses in different banana tissue, however at varying levels. The transcript levels of some of the banana HDZIV genes were also detected in banana fruit pulp, suggesting their putative role in fruit attributes. A large number of genes of this family showed modulated expression under drought and salinity stress. Taken together, the present work lays a foundation for elucidation of functional aspects of the banana HDZIV genes and for their possible use in the banana improvement programs.